A potent alpha-glucosidase inhibitor from Myristica cinnamomea King. (February 2016) - Sivasothy, Yasodha; Loo, Kong Yong; Leong, Kok Hoong; Litaudon, Marc; Awang, Khalijah
Graphical abstract: A new dimeric acylphenol, giganteone D (1 ) and an unprecedented acylphenol, cinnamomeone A (2 ) isolated from the bark of Myristica cinnamomea King exhibit α-glucosidase inhibitory activity. Highlights: A dimeric acylphenol, giganteone D, was isolated from Myristica cinnamomea . The bark also yielded an acylphenol with an unprecedented skeleton, cinnamomeone A. Isolates were tested for their α-glucosidase inhibiting potential. Giganteone D was identified as a potent α-glucosidase inhibitor. Abstract: A dimeric acylphenol and a potent α-glucosidase inhibitor, giganteone D (IC50 5.05 μM), was isolated and characterized from the bark of Myristica cinnamomea King. The bark also yielded an acylphenol with an unprecedented skeleton for which the name cinnamomeone A (IC50 358.80 μM) was proposed. Their structures were established by means of NMR and MS spectrometric analyses. The Lineweaver–Burk plot of giganteone D indicated that it was a mixed-type inhibitor. This is the first report on the α-glucosidase inhibiting potential of acylphenols.